Evidence for UHP anatexis in the Shuanghe UHP paragneiss from inclusions in clinozoisite, garnet, and zircon. (5th December 2019) - Liu, Qiang; Hermann, Jörg; Zheng, Shu; Zhang, Junfeng
Abstract: The Shuanghe garnet‐bearing paragneiss from the Dabie ultra‐high–pressure (UHP) orogen occurs as an interlayer within partially retrogressed eclogite. A first UHP metamorphic stage at 680°C, 3.8–4.1 GPa is documented by Zr‐in‐rutile temperatures coupled with phengite inclusions (Si = 3.55) in clinozoisite and grossular‐rich garnet. Relic matrix phengite and phengite inclusions in zircon rims display lower Si of 3.42. Combined with garnet compositions and Ti‐in‐zircon temperatures, they provide evidence for a second UHP metamorphic stage at 800–850°C, ~3.8 GPa. Such isobaric heating at UHP conditions has not been documented so far from the adjacent eclogites and other rock types in the Dabie orogen and indicates proximity to the hot, convecting mantle wedge. The dominant mineral assemblage consisting of plagioclase, epidote, biotite, and amphibole provides evidence for widespread retrogression during the exhumation of the UHP paragneiss. Several types of polyphase mineral inclusions were identified. Phengite inclusions hosted by clinozoisite are partially replaced by kyanite and K‐feldspar, whereas inclusions in host garnet consist of relic phengite, K‐feldspar, and garnet, indicating limited sub‐solidus dehydration of phengite by the reaction Ph→Kfs+Ky±Grt+fluid. Tightly intergrown K‐feldspar and quartz are preserved as inclusions with sharp boundaries and radial cracks in garnet. Analyses of whole inclusions also show small enrichments in light rare earth elements. These inclusions are interpreted to be derived from melting of an inclusion assemblage consisting of Ph+Coe±Czo. A third type of polyphase inclusion consists of typical nanogranite (Ab+Kfs+Qz±Ep) inclusions in recrystallized metamorphic zircon. Ti‐in‐zircon thermometry and the Si content of phengite included in these zircon domains indicate that melting occurred at 800–850°C and 3.8–4.0 GPa during isobaric heating at UHP conditions. The partial melting event led to an equilibration of trace elements in garnet, phengite, and apatite. Using published partition coefficients between these minerals and hydrous granitic melt, the trace element composition of the UHP anatectic melt can be constrained. The melts are characterized by high LILE contents and pronounced relative enrichments of U over Th and Ta over Nb. The REE are below primitive mantle values, likely due to the presence of residual clinozoisite and garnet during partial melting. So far, no major granitic bodies have been found that share the same trace element pattern as the partial melts from the UHP anatexis of the Shuanghe paragneiss.